The World Trade Organization And Antidumping In Developing Countries - Bown, Chad P., 1972- 1972- (The World Bank, 2006)
Since the 1995 inception of the World Trade Organization (WTO), developing countries have become some of the most frequent users of the WTO-sanctioned antidumping trade policy instrument. This paper exploits newly available data to examine the pattern of actual industrial use of antidumping in nine of the major "new user" developing countries - Argentina, Brazil, Colombia, India, Indonesia, Mexico, Peru, Turkey and Venezuela. For these countries we are able to match data from two newly available sources: data on production in 28 different 3-digit ISIC industries from the Trade, Production and Protection Database to data on antidumping investigations, outcomes and imports at the 6-digit Harmonized System (HS) product level from the Global Antidumping Database. Our econometric analysis is to estimate a two-stage model of the industry-level decision to pursue an antidumping investigation and the national government's decision of whether and how much antidumping import protection to provide. First, we find evidence consistent with the theory of endogenous trade policy: larger industries that face substantial import competition are more likely to pursue an antidumping investigation, and larger and more concentrated industries receive greater antidumping protection from imports. Second, we find that industries that use antidumping are more likely to face the changing economic conditions specified by the technical evidentiary criteria of the WTO Antidumping Agreement: industries that face rapidly falling import prices are more likely to pursue an investigation, and industries that are more susceptible to cyclical dumping due to greater capital investment expenditures and that face rapidly increasing competition from imports receive greater antidumping protection